Sub-monolayer film growth of a volatile lanthanide complex on metallic surfaces - Isshiki, Hironari; Chen, Jinjie; Edelmann, Kevin; Wulfhekel, Wulf (Beilstein Journal of Nanotechnology, 2015)
We deposited a volatile lanthanide complex, tris(2,2,6,6-tetramethyl-3,5-heptanedionato)terbium(III), onto metal surfaces of Cu(111), Ag(111) and Au(111) in vacuum and observed well-ordered sub-monolayer films with low temperature (5 K) scanning tunneling microscopy. The films show a distorted three-fold symmetry with a commensurate structure. Scanning tunneling spectroscopy reveals molecular orbitals delocalized on the ligands of the molecule. Our results imply that this complex can be transferred onto the metal substrates without molecular decomposition or contamination of the surface. This new rare-earth-based class of molecules broadens the choice of molecular magnets to study with scanning tunneling microscopy.
Keywords: β-diketonate; molecular films; scanning tunneling microscopy; terbium; volatile lanthanide complex

(untitled) - Gatteschi, D.; Sessoli, R. (Angew. Chem., Int. Ed., 2003)

(untitled) - Ishikawa, N.; Sugita, M.; Ishikawa, T.; Koshihara, S.; Kaizu, Y. (J. Am. Chem. Soc., 2003)

(untitled) - Heinrich, A. J.; Gupta, J. A.; Lutz, C. P.; Eigler, D. M. (Science, 2004)

(untitled) - Hirjibehedin, C. F.; Lin, C.-Y.; Otte, A. F.; Ternes, M.; Lutz, C. P.; Jones, B. A.; Heinrich, A. J. (Science, 2007)

(untitled) - Tsukahara, N.; Noto, K.-i.; Ohara, M.; Shiraki, S.; Takagi, N.; Takata, Y.; Miyawaki, J.; Taguchi, M.; Chainani, A.; Shin, S.; Kawai, M. (Phys. Rev. Lett., 2009)

(untitled) - Meier, F.; Zhou, L.; Wiebe, J.; Wiesendanger, R. (Science, 2008)

(untitled) - Fahrendorf, S.; Atodiresei, N.; Besson, C.; Caciuc, V.; Matthes, F.; Blügel, S.; Kögerler, P.; Burgler, D. E.; Schneider, C. M. (Nat. Commun., 2013)

(untitled) - Komeda, T.; Isshiki, H.; Liu, J.; Zhang, Y.-F.; Lorente, N.; Katoh, K.; Breedlove, B. K.; Yamashita, M. (Nat. Commun., 2011)

(untitled) - Vitali, L.; Fabris, S.; Conte, A. M.; Brink, S.; Ruben, M.; Baroni, S.; Kern, K. (Nano Lett., 2008)

(untitled) - Hampden-Smith, M. J.; Kodas, T. T. (Chem. Vap. Deposition, 1995)

(untitled) - Munery, S.; Ratel-Ramond, N.; Benjalal, Y.; Vernisse, L.; Guillermet, O.; Bouju, X.; Coratger, R.; Bonvoisin, J. (Eur. J. Inorg. Chem., 2011)

(untitled) - Sicre, J. E.; Dubois, J. T.; Eisentraut, K. J.; Sievers, R. E. (J. Am. Chem. Soc., 1969)

(untitled) - Sievers, R. E.; Sadlowski, J. E. (Science, 1978)

(untitled) - Sliznev, V. V.; Belova, N. V.; Girichev, G. V. (Comput. Theor. Chem., 2015)

(untitled) - Chilton, N. F.; Langley, S. K.; Moubaraki, B.; Soncini, A.; Batten, S. R.; Murray, K. S. (Chem. Sci., 2013)

(untitled) - Narasimhan, S.; Vanderbilt, D. (Phys. Rev. Lett., 1992)

(untitled) - Yokoyama, T.; Yokoyama, S.; Kamikado, T.; Okuno, Y.; Mashiko, S. (Nature, 2001)

(untitled) - Böhringer, M.; Morgenstern, K.; Schneider, W.-D.; Berndt, R.; Mauri, F.; De Vita, A.; Car, R. (Phys. Rev. Lett., 1999)

(untitled) - Davis, L. C.; Everson, M. P.; Jaklevic, R. C.; Shen, W. (Phys. Rev. B, 1991)

(untitled) - Crommie, M. F.; Lutz, C. P.; Eigler, D. M. (Nature, 1993)

(untitled) - Zhang, L.; Miyamachi, T.; Tomanić, T.; Dehm, R.; Wulfhekel, W. (Rev. Sci. Instrum., 2011)